Preventing the spread of COVID-19 in South Sudan - Eluzai Hakim (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2020)
COVID-19 is the illness caused by a new strain of coronavirus first identified in Wuhan City, China in December 2019. It can cause a persistent new onset cough and a high temperature. Based on data from relatively more affluent countries coronavirus can cause more severe symptoms in people with weakened immune systems, older people (over 60 years) and those with long term conditions like diabetes mellitus, cancer, chronic lung disease and high blood pressure. It is not known if it will be the same in South Sudan.